2022
DOI: 10.21203/rs.3.rs-2088288/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Choice Behaviour in Economic Games using Gaze Data Encoded as Scanpath Images

Abstract: Eye movement data has been extensively utilized by researchers interested in studying decision-making within the strategic setting of economic games. In this paper, we demonstrate both a deep learning and traditional machine learning classification method which are able to accurately identify a given participant's decision strategy before they commit to an action while playing games. Our approach focuses on creating scanpath images that best capture the dynamics of a participant's gaze behaviour during a given… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Using machine learning, we were able to accurately predict trialby-trial cooperation from four-fixation (three first and last) gaze sequences, with higher accuracy than using the first and last fixations only, showing the importance of studying gaze sequences. Scanpaths have been used in vision research to compare information-sampling patterns across individuals 75 or to improve users' experience in human-computer interactions 76 , and they have recently been applied to predict choices in economic games 77 . Here we showed that studying such paths in the context of cooperative decisions improves predictions of behavior and allows us to explain the effects of exogenous manipulations of attention on choices, by showing how positioning options at different locations on the screen modified key information sampling patterns, not limited to the first information subjects sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Using machine learning, we were able to accurately predict trialby-trial cooperation from four-fixation (three first and last) gaze sequences, with higher accuracy than using the first and last fixations only, showing the importance of studying gaze sequences. Scanpaths have been used in vision research to compare information-sampling patterns across individuals 75 or to improve users' experience in human-computer interactions 76 , and they have recently been applied to predict choices in economic games 77 . Here we showed that studying such paths in the context of cooperative decisions improves predictions of behavior and allows us to explain the effects of exogenous manipulations of attention on choices, by showing how positioning options at different locations on the screen modified key information sampling patterns, not limited to the first information subjects sampled.…”
Section: Discussionmentioning
confidence: 99%